2022
DOI: 10.15283/ijsc22141
|View full text |Cite
|
Sign up to set email alerts
|

The Calcineurin-Drp1-Mediated Mitochondrial Fragmentation Is Aligned with the Differentiation of c-Kit Cardiac Progenitor Cells

Abstract: Background and Objectives: The heart contains a pool of c-kit + progenitor cells which is believed to be able to regenerate. The differentiation of these progenitor cells is reliant on different physiological cues. Unraveling the underlying signals to direct differentiation of progenitor cells will be beneficial in controlling progenitor cell fate. In this regard, the role of the mitochondria in mediating cardiac progenitor cell fate remains unclear. Specifically, the association between changes in mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Damaged mitochondria release mitochondrial ROS and DNA into the cytosol, which acts as danger signals resulting in the hyperactivation of inflammatory signalling pathways [ 23 ]. Korski et al proposed that oxidative stress, mitochondrial dysfunction and cellular energy imbalance could arrest early proliferation of C-Kit + -CPCs (cardiac progenitor cells) [ 24 ]; Rahman et al also found pharmacologically inhibiting of mitochondrial fragmentation could retain the undifferentiated state of C-Kit + -CPCs [ 25 ]. Mitochondrial dysfunction is already assumed involved in the pathology of NASH with diverse mechanisms especially mitophagy (a selective autophagy eliminating damaged mitochondria to maintain mitochondrial homeostasis) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Damaged mitochondria release mitochondrial ROS and DNA into the cytosol, which acts as danger signals resulting in the hyperactivation of inflammatory signalling pathways [ 23 ]. Korski et al proposed that oxidative stress, mitochondrial dysfunction and cellular energy imbalance could arrest early proliferation of C-Kit + -CPCs (cardiac progenitor cells) [ 24 ]; Rahman et al also found pharmacologically inhibiting of mitochondrial fragmentation could retain the undifferentiated state of C-Kit + -CPCs [ 25 ]. Mitochondrial dysfunction is already assumed involved in the pathology of NASH with diverse mechanisms especially mitophagy (a selective autophagy eliminating damaged mitochondria to maintain mitochondrial homeostasis) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the differentiation process of c-kit + progenitor cells involves mitochondrial fragmentation, which is controlled by the calcineurin-Drp1 pathway [ 151 ], while an environmental stressor such as high glucose milieu can alter mitochondrial dynamics and increase the expression of fission-related proteins such as Fis1 and Drp1, leading to a significant decrease in the tube-forming ability of CPCs [ 152 ]. Interestingly, pharmacological inhibition of mitochondrial fragmentation can help to maintain the undifferentiated state of c-kit + progenitor cells.…”
Section: The Role Of Mitochondria In Heart Regenerationmentioning
confidence: 99%